2015
DOI: 10.1039/c5ta05127d
|View full text |Cite
|
Sign up to set email alerts
|

Capture and electrochemical conversion of CO2to ultrathin graphite sheets in CaCl2-based melts

Abstract: A novel method for capture and electrochemical conversion of CO2to graphite sheets in molten CaCl2with the utilization of renewable energy sources has been proposed. The reduction mechanism was investigated and the results indicate that two steps are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 40 publications
1
76
0
Order By: Relevance
“…al 11 The authors comment that the observed "nano ropes" observed are parallel carbon nanofibers bound together, though speculation of how the different carbon nanostructures are formed in electrolysis is not detailed in the report. In more recent years, the observation of higher quality carbon nanostructures has been studied, with the growth of few-layer graphene sheets (<5 layers) 15,16 ( Figure 5d) and carbon nanofibers with diameters >200 nm (Figure 5e) 58 in 2015, and more recently carbon nanotubes with diameters >100 nm (Figure 5f) 46 in 2016. These works begin to build upon mechanistic understandings gained from gas phase growth techniques, and start to bridge the gap between gas phase growth of carbon nanostructures and CO 2 electrolysis.…”
Section: Types Of Carbon Materials Produced From Comentioning
confidence: 99%
See 1 more Smart Citation
“…al 11 The authors comment that the observed "nano ropes" observed are parallel carbon nanofibers bound together, though speculation of how the different carbon nanostructures are formed in electrolysis is not detailed in the report. In more recent years, the observation of higher quality carbon nanostructures has been studied, with the growth of few-layer graphene sheets (<5 layers) 15,16 ( Figure 5d) and carbon nanofibers with diameters >200 nm (Figure 5e) 58 in 2015, and more recently carbon nanotubes with diameters >100 nm (Figure 5f) 46 in 2016. These works begin to build upon mechanistic understandings gained from gas phase growth techniques, and start to bridge the gap between gas phase growth of carbon nanostructures and CO 2 electrolysis.…”
Section: Types Of Carbon Materials Produced From Comentioning
confidence: 99%
“…[42][43][44][45] In contrast to this mature field, the growth of carbon nanostructures from the liquid-phase electrochemical reduction of CO 2 remains only a new field of research, with the most recent work demonstrating growth of large-diameter (>100 nm) CNTs 46 and fewlayer graphene flakes from CO 2 conversion. 15,16 These initial works demonstrate the capability to leverage CO 2 as a precursor in carbon nanostructure growth, even though forward-looking efforts to achieve high quality, precisely tuned materials such as single-walled CNTs or single-layered graphene at high yields will require control of the process beyond the systems-level approaches reported so far. This presents an exciting frontier that exists at the intersection of these two communities -those who have studied the mechanistic details of catalytic processes relating to nucleation and growth of nanostructures, and those who are focused on systems-level directions to develop platforms which can address important global issues.…”
mentioning
confidence: 99%
“…Molten salt CO 2 capture and electrochemical transformation (MSCC-ET) process is a preferable method for the conversion of CO 2 to advanced carbon materials [1,[16][17][18] . Electrons are the strongest reducing agent, guaranteeing a fast electrochemical reaction at mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, electrochemical conversion rate of CO 2 in aqueous solution is very low due to a low CO 2 solubility [20] . In addition, there is a competing reduction reactions for H 2 O, leading to a considerable current efficiency loss [16,18] . Furthermore, catalysts with complex structures are needed for CO 2 conversion in aqueous solutions [20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation